A novel fast reroute signaling cost for multicast proxy mobility - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Abdullah, Azween; Mohd. Ramli, Huda Adibah (American Scientific Publishers, 2017)
A profound analysis of signaling cost for multicast network mobility management environment. The evaluation is a innovative integration of Multicast only Fast Reroute (MFR) and Context Transfer (CT). This integration is implemented to network mobility environment which is Proxy Mobile IPv6 (PMIPv6). The signaling cost terms is described based on handover process flow of the proposed implementation. This paper introduces and validates a novel enhanced signaling cost procedure for multicast PMIPv6. This procedure helps to improve network mobility performance as mobile multicast traffic usage rises. Through this implementation better signaling cost formula is brought forward. The integration helps to ease usage increment issues.